Nicaragua : Report on Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This report assesses the Observance of Standards and Codes on the Fiscal Transparency Module for Nicaragua. Nicaragua has made notable progress in recent years in improving fiscal management and fiscal transparency. The public sector has been downsized and different branches and levels of government have been more clearly defined. The budget is providing more comprehensive information on the government's fiscal activities in the framework of institutional, programmatic, and economic classifications. The implementation of a financial management information system and a treasury single account are providing timely and more reliable information on budget execution and borrowing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet